2013 IEEE Conference on Open Systems (ICOS) 2013
DOI: 10.1109/icos.2013.6735040
|View full text |Cite
|
Sign up to set email alerts
|

Online signature verification using neural network and pearson correlation features

Abstract: In this paper, we proposed a method for feature extraction in online signature verification. We first used signature coordinate points and pen pressure of all signatures, which are available in the SIGMA database. Then, Pearson correlation coefficients were selected for feature extraction. The obtained features were used in back-propagation neural network for verification. The results indicate an accuracy of 82.42%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Results are verified by using back propagation neural network and the accuracy of 82.42% is obtained. Experimental results indicate the number of false acceptance is more than false rejection [10].…”
Section: Related Workmentioning
confidence: 96%
“…Results are verified by using back propagation neural network and the accuracy of 82.42% is obtained. Experimental results indicate the number of false acceptance is more than false rejection [10].…”
Section: Related Workmentioning
confidence: 96%
“…To improve the accuracy of signature verification, some studies [8][9][10] utilize machine learning techniques, which are one of the most noteworthy technologies. Similar to the process in feature-based signature verification, they use descriptive features of signatures for building a subject model.…”
Section: Related Workmentioning
confidence: 99%
“…Similar to the process in feature-based signature verification, they use descriptive features of signatures for building a subject model. Iranmanesh et al [9] exploited MLP for signature verification, and demonstrated an average accuracy of 82.42% for recognizing the subject; however, this method could not distinguish between imitated and original signatures. As mentioned previously, M. Fayyza et al [10] used AE, the one-class model, to distinguish imitated signatures.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations